2018
DOI: 10.1111/tmi.13046
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of syndromic management in targeting vaginal and cervical infections among symptomatic women of reproductive age attending primary care clinics in Dakar, Senegal

Abstract: This study highlights the limitations of the applicability of the WHO syndromic approach in settings with low prevalence of sexually transmitted infections (STIs) and calls for affordable and accurate rapid tests for STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
17
2
1
Order By: Relevance
“…Flowcharts were categorized as follows: flowchart 1 = history and risk assessment; flowchart 2 = history, risk assessment and speculum examination; flowchart 3 = history, risk assessment, speculum examination, and vaginal discharge samples for Gram staining and wet‐mount microscopy to diagnose the presence of budding yeast or psuedohyphae for Candida albicans , motile trichomonads for Trichomonas vaginalis (TV) and Amsel criteria for diagnosis of bacterial vaginosis (BV); and flowchart 4 = country‐adapted flowcharts with country‐specific risk factors or those not defined by the study methods. Four additional studies were added to the meta‐analysis . We conducted a meta‐analysis by pooling of samples from all studies within different types of flowcharts.…”
Section: Methodsmentioning
confidence: 99%
“…Flowcharts were categorized as follows: flowchart 1 = history and risk assessment; flowchart 2 = history, risk assessment and speculum examination; flowchart 3 = history, risk assessment, speculum examination, and vaginal discharge samples for Gram staining and wet‐mount microscopy to diagnose the presence of budding yeast or psuedohyphae for Candida albicans , motile trichomonads for Trichomonas vaginalis (TV) and Amsel criteria for diagnosis of bacterial vaginosis (BV); and flowchart 4 = country‐adapted flowcharts with country‐specific risk factors or those not defined by the study methods. Four additional studies were added to the meta‐analysis . We conducted a meta‐analysis by pooling of samples from all studies within different types of flowcharts.…”
Section: Methodsmentioning
confidence: 99%
“…[8,9] At present, the effectiveness of syndromic management on reduction of the prevalence of STI infections is not satisfactory. [10][11][12] The reason is not only because of its poor sensitivity, but more importantly, most STI infections such as CT and NG are asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…In many settings including Senegal, patients presenting at primary care units with signs suggestive of STI (urethral discharge, vaginal discharge syndromes) are often being diagnosed and managed presumptively using a syndromic approach based on WHO guidelines [15]. But studies have shown that a syndromic-based approach in some settings may lack sensitivity and specificity and can lead to mismanagement of several STI including trichomoniasis [16, 17]. In addition, biological confirmation of T. vaginalis infection in many primary care units remained at a low level due to lack of appropriate diagnostic tool and community prevalence data remained scarce [18, 19].…”
Section: Introductionmentioning
confidence: 99%